Systematic Review: How to reduce the car cabin temperature using solar energy? - Noor Al-Huda A.Taher; Ali A . F . Al- Hamadani (Wasit Journal of Engineering Sciences)
The two biggest issues we have are the energy crisis and global warming. Both issues are made worse by the use of traditional air conditioners. Therefore, numerous techniques were devised to overcome that, including solar ventilation, solar cooling, and solar thermoelectric modules. The most suitable choice was solar thermoelectric cooling because it was safe for the environment, provided a significant drop in car cabin temperatures, and avoided using hazardous refrigeration fluids.